Effects of Netbook and Tablet Usage Postures on the Development of Fatigue, Discomfort and Pain - Yassierli Yassierli; Anita Juraida (Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
The number of people using online tablets in public places has increased dramatically. Their postures are dominantly characterized by non-neutral and awkward positions that in the long term may lead to a higher risk of musculoskeletal disorders. The purpose of this study was to investigate the effects of tablet compared to laptop (i.e. netbook) usage postures on the development of fatigue, discomfort and pain. A total of 12 participants accomplished email typing tasks for 2 hours with four different usage configurations: 1) Netbook-on-table, 2) Netbook-on-lap, 3) Tablet-on-table, and 4) Tablet-on-lap. Changes in fatigue, discomfort, and pain were monitored based on pinch grip strength (tip pinch, key pinch, and palmar pinch), rating of perceived discomfort, and Phalen's & Reverse Phalen's tests, respectively. The results indicated that the effect of portable device placement was significant (p < 0.05), with varied effects across measurements. No effect of portable computer type was found. The interactive effect of portable computer type and placement was only significant for right tip pinch (p < 0.05). The findings of this study can hopefully be used to increase the awareness of tablet users about associated fatigue, discomfort and pain while using a tablet in public places that may lead to a higher risk of musculoskeletal disorders.